The effect of the NMDA receptor antagonist MK-801 on cerebral blood flow and infarct volume in experimental focal stroke. - Buchan, A; Slivka, A; Xue, D (1992)
The non-competitive N-methyl-D-aspartate receptor/channel antagonist dizocilipine maleate (MK-801) has been reported to reduce infarct volume in a variety of focal stroke models. We examined the effect of MK-801 on infarct volume and cerebral blood flow in temporary and permanent focal ischemia in rats. In Wistar rats exposed to permanent right common carotid artery and 2 h of transient right middle cerebral and left common carotid artery occlusion followed by 22 h of reperfusion, MK-801 reduced infarct volume by 73% (P less than 0.05) and significantly increased cerebral blood flow to the ischemic core throughout the 2-h period of ischemia. In spontaneously hypertensive rats (SHRs) exposed to permanent right common carotid artery occlusion and 2 h of transient right middle cerebral artery occlusion followed by 22 h of reperfusion, MK-801 decreased infarct volume by 13% (P greater than 0.05) and increased cerebral blood flow to the penumbral region. In SHRs subjected to permanent right common carotid and middle cerebral artery occlusion MK-801 reduced infarct volume by 18% at 3 h (P greater than 0.05), by 25% at 6 h (P less than 0.01) and by 18% at 24 h (P less than 0.05). MK-801-treated SHRs had no difference in cerebral blood flow to the ischemic core, but increased cerebral blood flow to penumbral zones as compared with untreated SHRs. These results suggest that the protective effect of MK-801, at least in part, relates to improved cerebral blood flow.